Agricultural strategy drafting retreat - Adeogun, Grace (International Food Policy Research Institute, 2009)
The Federal Ministry of Agriculture and Water Resources (FMAWR) is updating Nigeria's agricultural development strategy document to make it meet the requirement of evidence-based strategy formulation. In line with this goal, the FMAWR in collaboration with the International Food Policy Research Institute (IFPRI) organized a retreat to draft an update of the Nation's Agricultural Strategy, otherwise known as the National Food Security Program Document. The objectives of this workshop here to: - provide a background for the agriculture strategy document, discuss the framework for updating the document, - assign tasks to the different collaborators, and - begin the process of updating the agriculture strategy document with information collected by the participants on identified knowledge gaps. It was attended by 22 participants drawn from various government departments, research institutions and universities and was held at the National Food Reserve Agency (NFRA), Abuja on November 5-6, 2009.